Définir des indicateurs en milieu controversé : retour sur l’expertise scientifique « Algues vertes » en France - Magalie Bourblanc (VertigO, 2016)
The proliferation of green algae found on Brittany beaches (France) has been on the agenda since the 1980s, first as a local problem, then lately as a full-fledged national stake. This case study provides a striking illustration of the idea that ecological indicators are highly political entities. We follow the design of such indicators and analyze how intertwined political and scientific matters appear to be. To this effect, we put into perspective the process of scientifically elaborating ecological indicators and the political process of framing the public problems to which they can be related. The scientific expertise around green algae blooms has been characterized by strong controversies for a prolonged period of time, up until recently. We show the relative inefficiency of the demarcation work undertaken by the actors of the controversy. On the contrary, we underline the positive impact of adopting new intervention categories, validated by the State expertise that posits itself as a referee to stabilize the controversy.